Synergy Between Selective Serotonin Reuptake Inhibitors and α2-Adrenergic Receptor Antagonists in the Treatment of Depression: Pharmacological Rationale and Clinical Significance - Jukić, Marin (Engrami, 2026)
Selective serotonin reuptake inhibitors (SSRIs) represent the most commonly used pharmacotherapeutic strategy in the treatment of major depressive disorder. However, a substantial proportion of patients do not achieve remission, develop only a partial response, or remain burdened by residual symptoms, most commonly insomnia, anxiety, loss of appetite, sexual dysfunction, and gastrointestinal complaints. Combining SSRI antidepressants with α2-adrenergic receptor antagonists, among which mirtazapine is the most important clinical representative, is a pharmacologically rational approach because it simultaneously enhances serotonergic transmission through complementary mechanisms and adds a noradrenergic component to antidepressant action. While SSRIs increase the synaptic availability of serotonin by inhibiting the serotonin transporter, mirtazapine increases the release of noradrenaline and serotonin by blocking presynaptic α2-autoreceptors and α2-heteroreceptors. In addition, antagonism of 5-HT2 and 5-HT3 receptors functionally directs serotonergic transmission toward 5-HT1A-mediated effects and may contribute to better tolerability compared with pure serotonergic potentiation. The clinical significance of this combination is most evident in patients with a partial response to SSRIs, depression accompanied by insomnia, anxiety, loss of appetite, or adverse effects of SSRI therapy. However, although randomized studies and meta-analyses generally indicate greater efficacy of combinations that include α2-receptor antagonists, some studies, such as the MIR trial, did not demonstrate a significant benefit of adding mirtazapine to ongoing SSRI therapy in all patients with SSRI-resistant depression. Therefore, the combination of an SSRI and mirtazapine should be regarded as a personalized, symptom-guided, and pharmacologically grounded strategy, rather than as a universally superior therapeutic approach.